2019
DOI: 10.1093/jme/tjz227
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and Dengue Mosquito Vectors from Lao PDR Show a Lack of the rdl Mutant Allele Responsible for Cyclodiene Insecticide Resistance

Abstract: The gamma-aminobutyric acid (GABA) receptor, RDL, plays important roles in neuronal signaling and is the target of highly effective insecticides. A mutation in RDL, commonly A296S, underlies resistance to several insecticides such as cyclodienes. Even though the use of cyclodienes has been banned, the occurrence of mutations substituting A296 is notably high in mosquitoes from several countries. Here, we report a survey investigating the prevalence of the Rdl mutant allele in mosquitoes from Laos, a country wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Variants occurring at a frequency of more than 2% in at least one of the four populations are reported in the known insecticide-resistance-associated genes Ace1 , Rdl , KDR , and GSTe2 (Supplementary Data 2 ). GSTe2 mutants are present in multiple populations, at a low rate, and there are a few individuals in Thmar Da and Preah Vihear with the Rdl resistance mutation, which is known to confer resistance to cyclodiene insecticides, despite evidence from other studies that species in this region lack this resistance mutation 32 . We did not investigate copy number variation, which is one mechanism by which GSTe2 confers insecticide resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Variants occurring at a frequency of more than 2% in at least one of the four populations are reported in the known insecticide-resistance-associated genes Ace1 , Rdl , KDR , and GSTe2 (Supplementary Data 2 ). GSTe2 mutants are present in multiple populations, at a low rate, and there are a few individuals in Thmar Da and Preah Vihear with the Rdl resistance mutation, which is known to confer resistance to cyclodiene insecticides, despite evidence from other studies that species in this region lack this resistance mutation 32 . We did not investigate copy number variation, which is one mechanism by which GSTe2 confers insecticide resistance.…”
Section: Resultsmentioning
confidence: 99%
“…gambiae, which are showing resistance to pyrethroids (Ngufor et al, 2017). A similar strategy could be used for insecticides that act on γ-aminobutyric acid (GABA) receptors, such as fipronil, especially considering that it has been shown that Aedes mosquitoes in Laos lack a mutation at A296 in the GABA receptor, resistance to dieldrin (RDL), which underlies insecticide resistance (Marcombe et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…gambiae , which are showing resistance to pyrethroids (Ngufor et al, 2017 ). A similar strategy could be used for insecticides that act on γ‐aminobutyric acid (GABA) receptors, such as fipronil, especially considering that it has been shown that Aedes mosquitoes in Laos lack a mutation at A296 in the GABA receptor, resistance to dieldrin (RDL), which underlies insecticide resistance (Marcombe et al, 2020 ). A combination of fipronil and permethrin has been shown to provide highly effective inhibition of feeding as well as considerable insecticidal efficacy against Aedes mosquitoes on dogs for at least four weeks, which may aid in the control of mosquitoes in the vicinity of treated domesticated animals (Fankhauser et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Variants occurring at a frequency of more than 2% in at least one of the four populations are reported in the known insecticide-resistance associated genes Ace1, Rdl, KDR, and GSTe2 (Supplementary Table 2). GSTe2 mutants are present in multiple populations, at a low rate, and there are a few individuals in Thmar Da and Preah Vihear with the Rdl resistance mutation, which is known to confer resistance to cyclodiene insecticides, despite evidence from other studies that species in this region lack this resistance mutation (32). We did not investigate copy number variation, which is one mechanism by which GSTe2 confers insecticide resistance.…”
Section: Insecticide Resistancementioning
confidence: 99%